Dining in Blue Light Impairs the Appetite of Some Leaf Epiphytes - Alsanius, Beatrix W.; Vaas, Lea; Gharaie, Samareh; Karlsson, Maria E.; Rosberg, Anna Karin; Wohanka, Walter; Khalil, Sammar; Windstam, Sofia (Frontiers in Microbiology, 2021)
(1) Background: The phyllosphere is subjected to fluctuating abiotic conditions. This study examined the phenotypic plasticity (PP) of four selected non-phototrophic phyllosphere bacteria (control strain: Pseudomonas sp. DR 5-09; Pseudomonas agarici, Bacillus thuringiensis serovar israeliensis (Bti) and Streptomyces griseoviridis (SG)) regarding their respiration patterns and surfactant activity as affected by light spectrum and nutrient supply. (2) Methods: The strains’ PP was examined under four light regimes (darkness (control); monochromatic light-emitting diodes (LED) at 460 nm (blue) and 660 nm (red); continuously polychromatic white LEDs), in the presence of 379 substrates and conditions. (3) Results: Light treatment affected the studied bacterial strain regarding substrate utilization (Pseudomonas strains > SG > Bti). Blue LEDs provoked the most pronounced impact on the phenotypic reaction norms of the Pseudomonas strains and Bti. The two Gram-positive strains Bti and SG, respectively, revealed inconsistent biosurfactant formation in all cases. Biosurfactant formation by both Pseudomonas strains was supported by most substrates incubated in darkness, and blue LED exposure altered the surface activity profoundly. Blue and white LEDs enhanced biofilm formation in PA in highly utilized C-sources. Putative blue light receptor proteins were found in both Pseudomonas strains, showing 91% similarity with the sequence from NCBI accession number WP_064119393. (4) Conclusions: Light quality–nutrient interactions affect biosurfactant activity and biofilm formation of some non-phototrophic phyllosphere bacteria and are thus crucial for dynamics of the phyllosphere microbiome.